A systematic review of perinatal social support interventions for asylum-seeking and refugee women residing in Europe - Balaam, M.C. (2021)
Yes === Asylum-seeking and refugee women currently residing in Europe face unique challenges in the perinatal period. A range of social support interventions have been developed to address these challenges. However, little is known about which women value and why. A critical interpretive synthesis was undertaken using peer reviewed and grey literature to explore the nature, context and impact of these perinatal social support interventions on the wellbeing of asylum-seeking and refugee women. Four types of interventions were identified which had varying impacts on women’s experiences. The impacts of the interventions were synthesised into five themes: Alleviation of being alone, Safety and trust, Practical knowledge and learning, being cared for and emotional support, and increased confidence in and beyond the intervention. The interventions which were most valued by women were those using a community-based befriending/peer support approach as these provided the most holistic approach to addressing women’s needs.